Dramma per musica eller musica per dramma? Mozarts Idomeneo – en seria som musikalsk opus - Barnholdt Hansen, Jette (Danish Yearbook of Musicology, 2003)
Mozart’s Idomeneo (1781) can be seen as a confirmation of the Italian opera seria, because the fundamental conventions of the genre are retained. But since Mozart was also inspired by contemporary French opera, Idomeneo possesses a consistent dramatic continuity within the musical texture that must have seemed strange to an audience expecting a traditional seria. In the article, Idomeneo is therefore described as the result of a constructive dialogue between old and new factors from a perspective of genre, and the main aim is to show that the Italian and French elements of style are of equal importance. Mozart’s musical characterisation of la seconda donna Elettra is used as an example. By uniting old Italian elements and new French ones, Mozart seems to be depicting tragic pathos in his musical portrait of this flaming woman. In the Baroque, opera seria was part of a culture of performance with a focus on bel canto; however, Mozart’s Idomeneo appears, to a considerable extent, to be an independent musical opus, where both the dramatic progress and the individuality of the characters are expressed by the musical development. The comments of the German composer, Johann Friedrich Reichardt from 1806 on Simrock’s newly published Idomeneo score, are therefore significant. He uses terms such as “Meisterwerk” (masterpiece) and “Kunstwerk” (work of art) – concepts that express a new aesthetic understanding based on autonomy. They had not been used previously in the seria reception, as the genre was primarily linked to and understood as performance.